Hunger and Self-Fashioning in Richard Wright’s Black Boy and Knut Hamsun’s Sult - Rees, Daniel (Current Objectives of Postgraduate American Studies, 2012)
Despite their obvious differences in style, setting, and literary background, Richard Wright’s novel Black Boy “and Knut Hamsun’s Sult“ share a marked similarity in their contemplation of hunger as both a social and existential issue. This matter is one that is bound up with the creation and understanding of self-fashioning and identity, as related through the subjective perceptions and experiences of the narrator.